General Lewis B. Hershey and Conscientious Objection during World War II - Krehbiel, Nicholas A. (Book collections on Project MUSE., 2011)
"This work examines ... how the duty of service to the state during wartime, a central feature of the citizen soldier in the American military tradition, extended even to those who objected during World War II"--Page 4